Human hippocampal theta–gamma coupling coordinates sequential planning during navigation - Zimo Huang; James A. Bisby; Neil Burgess; Daniel Bush (Proceedings of the National Academy of Sciences, 2026)
Human behavior often relies on executing a specific sequence of actions to achieve a desired outcome. However, the neural mechanisms underlying the dynamic construction and maintenance of such sequences during goal-directed behavior are not yet clear. Empirical and theoretical studies of working memory function suggest that sequential information may be encoded in neural circuits by bursts of gamma activity occurring at consecutive theta phases. Here, we asked whether a similar coding scheme might support sequential planning during goal-directed navigation. Using noninvasive magnetoencephalography and an abstract navigation task, we found that hippocampal theta power during both planning and subsequent navigation decreased with proximity to the current goal, only during accurate navigation. At the same time, theta–gamma phase–amplitude coupling (PAC) increased with goal proximity, consistent with sequences of upcoming locations being represented by gamma bursts occurring at successive theta phases. Importantly, entorhinal high gamma and hippocampal low gamma dominated while traversing novel and previously experienced paths, respectively, consistent with previous rodent studies. These findings suggest that hippocampal theta–gamma PAC flexibly and dynamically coordinates sequences of actions during goal-directed behavior across mammalian species, using different gamma bands for mnemonic and prospective planning.